ESTUDO DAS FORMAS E DIMENSÕES LINGUAIS DAS ARCADAS DENTÁRIAS EM INDIVÍDUOS BRASILEIROS COM OCLUSÃO NORMAL - Miyahira, Yasushi Inoue (2007)
The concern with the study of dental arches shapes and dimensions has been always present in the orthodontic science. The first article published on lingual orthodontics, a technique which arose in the last 1970s, was authored by Fujita and discussed the dental arch wire form to be used and described it as like as a mushroom form. Despite the fact that this technique has been spread more intensively in recent years as a definite and efficient esthetic solution, the related studies has focused mainly on new materials manufacturing, lingual appliances installation techniques and clinical solutions, with few mentions on dental arches morphology. The present research work objects to study dental arches shapes and dimensions in leucoderm subjects with normal occlusion. Forty seven pairs of normal occlusion dental casts (either upper and lower arches) were used, all were trimmed and digitalized for better examining of the occlusal surfaces. Reference points were marked as well as some virtual ones were created to make possible the measurements, that was accomplished using the CorelDraw 12 computer software. The results determined three lingual dental arch forms: mushroom, Christmas tree and a mix of the two. The Christmas tree arch form showed the major prevalence as a whole, but when the samples were analyzed separately, that is the upper and lower lingual arches, it was found a major prevalence of the mushroom arch form in the upper arches and, conversely, a Christmas tree arch form in the lower ones. As a consequence, this was the greater combination among upper and lower lingual dental arches. Considering this result we proposed the build up of templates for lingual orthodontic arch wires shaping, based on the sample values, determining quarters 1, average and 3, as the values to define sizes small, medium and large.